Maerua koratensis (Capparaceae), a new species from Thailand - Srisanga, Prachaya; Muangsan, Nooduan; Choopan, Thiamhathai; Thangthong, Jakrapong; Pratcharoenwanich, Ratchada; Watthana, Santi (Phytotaxa, 2021)
A new species, Maerua koratensis (Capparaceae), only known from a restricted locality in Nakhon Ratchasima Province, eastern Thailand, is here described and illustrated. This is the second species of Maerua to be described from South-East Asia. This new species is distinguished by the simple leaves, petaliferous flowers with distinctly 4-lobed laciniate disc, and cylindrical, torulose to moniliform fruits. Morphological characteristics of M. koratensis and M. juncea subsp. juncea, its most similar, are compared. A key to the Maerua species occurring in mainland South-East Asia is provided.